ENHANCING SOCIAL STUDIES LEARNING OUTCOMES THROUGH PROBLEM-BASED LEARNING IN AN ISLAMIC INTEGRATED ELEMENTARY SCHOOL - Irwan Satria; Aziza Aryati; Nova Asvio; Muhammad Mujtaba Asad (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to investigate the influence of spiritual motivation and institutional support on teaching efficacy among volunteer teachers in pesantren across Jambi Province, Indonesia. A cross-sectional survey design was employed, involving 218 volunteer teachers from 24 pesantren. Data were collected using adapted instruments measuring spiritual motivation, perceived institutional support, basic psychological needs satisfaction (autonomy, competence, relatedness), and teaching efficacy. Structural equation modeling (SEM) with partial least squares (PLS-SEM) was used for data analysis. The results reveal that spiritual motivation significantly and positively influenced teaching efficacy (β = 0.39, p < 0.001), both directly and through the mediation of satisfaction of basic psychological needs. Institutional support also exerted a significant positive effect on teaching efficacy (β = 0.31, p < 0.001), primarily mediated by the satisfaction of competence and relatedness needs. The interaction between spiritual motivation and institutional support produced a synergistic effect that enhances the fulfillment of all three basic psychological needs. These findings extended SDT by demonstrating that spiritually grounded intrinsic motivation, when coupled with structured institutional support, creates an optimal motivational ecology for volunteer teachers in faith-based educational settings. The implications of this study indicated that PBL can be used as an effective alternative learning model to improve students’ learning outcomes and social attitudes in Islamic integrated elementary schools